Аналіз систем моніторінгу несанкціонованого доступу до приміщення - Чеснаков, Б. О. (ХНУРЕ, 2022)
This work is devoted to familiarization with protection automatic systems. The security system is an automated complex designed to protect houses. Different types and devices of protection and their functionality are considered. Security system components are considered. Analysis of the required sensors and the effectiveness of these different options for security systems is done.
Keywords: системи моніторингу; несанкціонований доступ